2020
DOI: 10.1111/nph.16589
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Arabidopsis HUA‐PEP gene activity reveals that ovule fate specification requires restriction of the floral A‐function

Abstract: Ovules are essential for sexual plant reproduction and seed formation, and are fundamental for agriculture. However, our understanding of the molecular mechanisms governing ovule development is far from complete. In Arabidopsis, ovule identity is determined by homeotic MADS-domain proteins that define the floral C-(AG) and D-(SHP1/SHP2, STK) functions. Pre-mRNA processing of these genes is critical and mediated by HUA-PEP activity, composed of genes encoding RNA-binding proteins. In strong hua-pep mutants, fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…The ovules are specified by AG-SEPs-STK/SHPs, while the carpels are specified by AG-SEPs. The balance between the two kinds of complexes is important for the specification of ovule identity [13][14][15] . Under normal temperature (22 °C), TCPs interacts with BEL1 and AG-SEPs to inhibit the activity of AG-SEPs in wild type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ovules are specified by AG-SEPs-STK/SHPs, while the carpels are specified by AG-SEPs. The balance between the two kinds of complexes is important for the specification of ovule identity [13][14][15] . Under normal temperature (22 °C), TCPs interacts with BEL1 and AG-SEPs to inhibit the activity of AG-SEPs in wild type.…”
Section: Discussionmentioning
confidence: 99%
“…The co-existence of SEPs, AG, STK and SHPs suggests that the AG-SEPs-STK/SHPs quartets specifying ovule identity co-exist in the ovules with AG-SEPs quartets specifying carpel identity, suggesting that regulatory mechanisms exert tight control over the activity of AG-SEPs-STK/SHPs quartets and AG-SEPs quartets to promote ovule identity, but not carpel identity, in ovules. Genetic analysis has shown that the activity of AG-SEPs-STK/SHPs quartets and AG-SEPs quartets, and the balance between them, are essential for the specification of ovules [13][14][15] . It has been shown that ag single mutants, sep1 sep2 sep3 triple mutants and sep1 sep2 sep3 sep4 quadruple mutants do not form carpels or ovules because they lack both types of quartets [16][17][18] .…”
mentioning
confidence: 99%